FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA PEGAWAI BANK SYARIAH MANDIRI DI KOTA MEDAN - Hasbidin Hasbidin (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2017)
This study examined the factors that affect the performance of employees. Variables into these factors are leadership, individual mechanism and the Company's policies, while the consequent variable is the performance of employees. The object of research are employees of PT. Bank Syariah Mandiri in Medan. Samples were treated in the study of 174 employees. Data analysis technique using Structural Equation Model using version 8.8 lisrel Student program. The research findings indicate that the mechanism through indicators invidual motivation, ability, competence and job stress is more influential and instrumental in improving employee performance, while leadership and corporate policy does not affect the performance of employees. Results if the data using lisrel 8.8 shows the relationship between the individual and the mechanism of employee performance significantly and positively influence on employee performance. Simultaneously leadership, individual mechanism and company policies affect the performance of employees of PT Bank Syariah Mandiri in Medan.